Development and application of fit manufacturing value stream mapping for production line improvement in frutania - Gwee, Wan Theng (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The purpose of this research is to develop a nem framwork which integrates the Fit manufacturing with the value stream mapping (VSM) namely Fit-VSM. The fit manufacturing integrates the principle from Lean manufacturing, Agility manufacturing and Sustainability manufacturing. Since there is a lack of intergrating the Fit principle into a continuous improvement for the production line, this framwork has to be developed